2019
DOI: 10.22478/ufpb.2317-6032.2019v23n1.35390
|View full text |Cite
|
Sign up to set email alerts
|

[Id 35390] Tuberculose Em População Indígena Autodeclarada No Estado Do Paraná

Abstract: Objetivo: Objetivou-se calcular e analisar o coeficiente de incidência e o percentual de cura da tuberculose na população indígena no estado do Paraná. Metodologia: Trata-se de um estudo epidemiológico retrospectivo realizado a partir de 36.889 casos de tuberculose obtidos por meio do Sistema de Informação de Agravos de Notificação do estado do Paraná no período de 2001 a 2012. Foram selecionadas variáveis clínicas contemplando dados da população indígena notificada com tuberculose no Estado do Paraná, forma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 11 publications
0
3
0
10
Order By: Relevance
“…From this perspective, it was observed that the epidemiological profile of those communities contributes to the spread of the disease due to unfavorable economic conditions and precarious basic sanitation present in some villages. [26][27] The causes of the presence of such diseases were inferred to be the imbalance of territorial invasions in the Legal Amazon and the insertion of life habits of non-indigenous people in urban and rural areas. 5,28 It was observed in this study that gender representativeness was illustrated by Brazilian indigenous women, by the power and participation of women in politics and in work in an indigenous community in the state of Mato Grosso do Sul.…”
Section: VImentioning
confidence: 99%
“…From this perspective, it was observed that the epidemiological profile of those communities contributes to the spread of the disease due to unfavorable economic conditions and precarious basic sanitation present in some villages. [26][27] The causes of the presence of such diseases were inferred to be the imbalance of territorial invasions in the Legal Amazon and the insertion of life habits of non-indigenous people in urban and rural areas. 5,28 It was observed in this study that gender representativeness was illustrated by Brazilian indigenous women, by the power and participation of women in politics and in work in an indigenous community in the state of Mato Grosso do Sul.…”
Section: VImentioning
confidence: 99%
“…Da mesma forma, evidencia-se a escassez de ações sanitárias, especialmente as que viabilizem o acesso à água tratada e encanada, o que pode resultar em alto risco de contrair outras enfermidades, como diarréia e parasitoses. Ainda, comprova a baixa escolaridade, pois evidências científicas constatam que indivíduos não alfabetizados apresentam maiores possibilidades de serem afetados pela doença, além de terem pouca propensão pela procura de serviços de saúde (Zorzi et al, 2019).…”
Section: A) Questões Socioeconômicasunclassified
“…Logo, é necessário que ocorra uma adaptação entre os profissionais que irão estar com a população indígena em busca de um resultado conclusivo, desde materiais e pessoas que possam facilitar a comunicação, o que nem sempre é possível (Malacarne et al, 2019b;Zorzi et al, 2019).…”
Section: B) Imprecisão Diagnósticaunclassified
See 2 more Smart Citations